Avaliação in vitro e ex vivo de oxigenador de membrana de baixa resistência para o uso ECMO sem auxílio de bomba - Gandolfi, José Francisco (2006)
Extracorporeal pulmonary assistance has been proposed as an invasive alternative to the conventional treatment when adequate oxygenation becomes impossible by mechanical ventilation. Extracorporeal membrane oxygenation (ECMO) attained using assisted circulation may cause hemolysis, coagulation disorders, an inflammatory response and complications inherent to a high-risk high-cost procedure. The objective of this work was to evaluate the efficacy, both in vitro and ex vivo, of a low-resistance oxygenator in ECMO without assisted circulation. Material and Method: Initially, different prototypes of the low-resistance membrane oxygenator were developed to test the influence of the of inlet and outlet conditions of the blood, the area, the quantity and placement of the fibers in the oxygenation process and the removal of carbon dioxide gas (CO2). In the in vitro tests when bovine blood was utilized, the mean flow, volume of blood needed to fill the oxygenator and for priming, oxygen saturation, carbon dioxide gas exchange and the pressure gradient were measured. For the ex vivo experiments, five Santa Inês sheep, weighing between 5 and 33 kg, were used. In each animal, variations in respect to the oxygen saturation, the PO2 and the PCO2 were studied in the systemic blood at the outlet of the oxygenator and of the venous blood using oxygen flow rates of 0.5L/min, 1.0 L/min and 1.5 L/min. Results: The oxygenator had an excellent mechanical performance, which was seen by the PO2, PCO2 and oxygen saturation of the blood at the outlet of the oxygenator. From the clinical point of view, the improvement in the PO2 and oxygen saturation and the reduction in PCO2 of the systemic arterial blood (femoral artery of the sheep), were evident in the five sheep. A tendency of better results was seen when the weight was less than 10kg. Translating these relationships in terms of blood flow and total volume, the best results appeared when the blood flow in the oxygenator/volume proportion was 20% or greater, establishing this cutoff point as the ideal flow necessary for the best performance of the oxygenator. Conclusion: The in vitro and ex vivo performance tests achieved with the low-resistance membrane oxygenator used in arteriovenous extracorporeal circulation without the assistance of a propulsion pump, proved that this device is capable of providing oxygen and removing carbon dioxide from the blood in sufficient quantities to maintain the tested parameters at acceptable limits when ventilation is prejudiced.